Delayed tooth replantation after root surface treatment with papain and sodium fluoride in rats: A histological and histomorphometrical evaluation - Vendrame Dos Santos, Cláudia Letícia [UNESP] (2020)
Introduction: The aim of this study was to examine the histological effect of papain and sodium fluoride in delayed replantation of rat incisor teeth on the repair process. Methods and Materials: Forty upper incisors of Wistar rats were randomly assigned to four groups (n=10). In group I, the dental papilla and the pulp tissue of extracted teeth were removed before immediate replantation in their sockets. In the other groups, the extracted teeth were maintained in dry storage for 60 min and subjected to different root surface treatments. In group II, the teeth were immersed in 10% papain for 20 min, scrubbed with gauze soaked in saline for 1 min, and immersed in a 2% acidulated- phosphate sodium fluoride solution for 20 min. In group III, the teeth were immersed in saline for 20 min, scrubbed with gauze soaked in saline for 1 min, and immersed in a 2% acidulated-phosphate sodium fluoride solution for 20 min. In group IV, root surface treatment was not applied. The root canals were treated and filled with a calcium hydroxide paste and the teeth were replanted. The animals were euthanized after 60 days and anatomic specimens containing the teeth were subjected to routine histochemical processing and staining with hematoxylin and eosin. The Kruskal-Wallis test was used, followed by the Dunn’s test for multiple comparisons. Results: Groups I and II had less inflammatory root resorption and total area of root resorption (P<0.05) than groups III and IV respectively. Conclusions: Based on this animal study, root surface treatment with papain and sodium fluoride in delayed tooth replantation showed greater efficaq’ in controlling inflammatory root resorption and may be a viable option for clinical application.